Oxidation of the Mycobacterium tuberculosis key virulence factor protein tyrosine phosphatase A (MptpA) reduces its phosphatase activity. Issue 12 (15th April 2022) - Niesteruk, Anna; Sreeramulu, Sridhar; Jonker, Hendrik R. A.; Richter, Christian; Schwalbe, Harald
Abstract : The Mycobacterium tuberculosis tyrosine‐specific phosphatase MptpA and its cognate kinase PtkA are prospective targets for anti‐tuberculosis drugs as they interact with the host defense response within the macrophages. Although both are structurally well‐characterized, the functional mechanism regulating their activity remains poorly understood. Here, we investigate the effect of post‐translational oxidation in regulating the function of MptpA. Treatment of MptpA with H2 O2 /NaHCO3, mimicking cellular oxidative stress conditions, leads to oxidation of the catalytic cysteine (C11) and to a conformational rearrangement of the phosphorylation loop (D‐loop) by repositioning the conserved tyrosine 128 (Y128) and generating a temporarily inactive preclosed state of the phosphatase. Thus, the catalytic cysteine in the P‐loop acts as a redox switch and regulates the phosphatase activity of MptpA. Abstract : In this study, we delineated the redox regulation mechanism of the Mycobacterium tuberculosis key virulence factor protein tyrosine phosphatase A (MptpA). Treatment of MptpA with H2 O2, mimicking cellular oxidative stress conditions, leads to oxidation of the catalytic cysteine (C11) and conformational rearrangement of the conserved tyrosine 128 (Y128), thereby reducing temporarily the activity of the bacterial phosphatase.